The effect of different fat content fish feed on the production parameters and meat quality of the hybrid striped bass - Juhász, Péter; Bársony, Péter; Csorvási, Éva; Szűcs, István; Remenyik, Judit; Stündl, László (Acta Agraria Debreceniensis, 2013)
The interspecific ’hybrid striped bass’ is the result of cross breeding. Their offspring have got good chances of growth and tolerate extreme water temperatures and the content of dissolute oxygen more than their parents. Furthermore, they are more resistant to diseases. Therefore, the hybrid is perfectly suitable for intensive fishery production. Our experiment lasted for seven weeks. We analysed the indices of growth and production of the hybrid as the consequence of nurturing them with two feeds of high nutritive value during this period. We examined the content of fat and of fatty acids in the flesh of these fish. There were no considerable differences in terms of weight gain, feed conversion ratio and uneven growth between the two groups, while survival was less likely among the the fish which had consumed more fat. We demonstrated, examining the flesh of the individuals which had consumed feed containing lower fat content, that it was fattier and contained more dry matter than those that had been fed of higher fat content. Besides, the content of omega-3 and omega-6 fatty acids was higher in the fish that had consumed less lipids.